The Relationship Between Clinical and Quantitative Measures of Pain Sensitization in Knee Osteoarthritis. Issue 5 (May 2020) - Moore, Rachel L.; Clifford, Amanda M.; Moloney, Niamh; Doody, Catherine; Smart, Keith M.; O'Leary, Helen
Abstract : Objectives: Pain sensitization in knee osteoarthritis (OA) is associated with greater symptom severity and poorer clinical outcomes. Measures that identify pain sensitization and are accessible to use in clinical practice have been suggested to enable more targeted treatments. This merits further investigation. This study examines the relationship between quantitative sensory testing (QST) and clinical measures of pain sensitization in people with knee OA. Methods: A secondary analysis of data from 134 participants with knee OA was performed. Clinical measures included: manual tender point count (MTPC), the Central Sensitization Inventory (CSI) to capture centrally mediated comorbidities, number of painful sites on a body chart, and neuropathic pain-like symptoms assessed using the modified PainDetect Questionnaire. Relationships between clinical measures and QST measures of pressure pain thresholds (PPTs), temporal summation, and conditioned pain modulation were investigated using correlation and multivariable regression analyses. Results: Fair to moderate correlations, ranging from −0.331 to −0.577 ( P <0.05), were identified between MTPC, the CSI, number of painful sites, and PPTs. Fair correlations, ranging from 0.28 to 0.30 ( P <0.01), were identified between MTPC, the CSI, number of painful sites, and conditioned pain modulation. Correlations between the clinical and self-reported measures and temporal summation were weak and inconsistent (0.09 to 0.25). In adjusted regression models, MTPC was the only clinical measure consistently associated with QST and accounted for 11% to 12% of the variance in PPTs. Discussion: MTPC demonstrated the strongest associations with QST measures and may be the most promising proxy measure to detect pain sensitization clinically.